The Influence of the Peer Learning Method on the Learning of Aqidah and Akhlak on the Social Empathy of Class X Students - Dita Karina Putri; Bella Aulia Ali Kurniawati (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to analyze the effect of peer learning method in learning Akidah Akhlak on increasing social empathy of grade X students at Madrasah Aliyah. This study uses a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The subjects of this study consisted of two groups, namely the experimental class and the control class selected through purposive sampling techniques. Data collection was carried out through observation and a Likert-scale-based social empathy questionnaire given at the pre-intervention and post-intervention stages. Data were analyzed using a t-test to see significant differences between the two groups. The results of this study indicate that the average social empathy score of students in the experimental class increased significantly from 66.1 in the pre-intervention to 84.2 in the post-intervention, while the control class only experienced an increase from 64.5 to 70.5. The results of the t-test show a significance value of 0.000 <0.05, which indicates a significant difference between the two groups. These findings prove that the peer learning method is effective in increasing students' social empathy through collaborative, dialogic, and participatory peer interactions. Therefore, the peer learning method is recommended as a learning strategy for Akidah Akhlak to strengthen students' social character and empathetic values.